Synthesis, Cytotoxicity Evaluation and Molecular Docking Study of N-Phenylpyrazoline Derivatives - Artania Adnin Tri Suma; Tutik Dwi Wahyuningsih; Mustofa Mustofa (Indonesian Journal of Chemistry, 2019)
The synthesis of N-phenylpyrazolines 1-5 was performed by the cyclocondensation of phenylhydrazine and appropriate chalcones that have been synthesized from our previous work. All of the compounds were elucidated for their structure using GC-MS, FTIR, 1H, and 13C-NMR spectrometers. Their anticancer activity was evaluated against breast cancer cell line (T47D) and colorectal cancer cell line (WiDr). Compound 4 (4-(3-(4-chlorophenyl)-1-phenyl-4,5-dihydro-1H-pyrazol-5-yl)-2-methoxyphenol) was found to be the most potent compound with IC50 value of 13.11 µg/mL in T47D cell line and 3.29 µg/mL in WiDr cell line. Docking study was conducted to evaluate the interaction between all compounds and EGFR receptor on cancer cells. Among the tested compounds, compound 4 is the only compound that has interaction with MET769 residue through hydrogen bonding due to the presence of hydroxyl group on its structure. Our findings suggest that the synthesized N-phenylpyrazolines in this study have a promising anticancer activity.